Adipose Tissue-Specific Deletion of 12/15-Lipoxygenase Protects Mice from the Consequences of a High-Fat Diet - Banumathi K. Cole; Margaret A. Morris; Wojciech J. Grzesik; Kendall A. Leone; Jerry L. Nadler (Mediators of Inflammation)
Type 2 diabetes is associated with obesity, insulin resistance, and inflammation in adipose tissue. 12/15-Lipoxygenase (12/15-LO) generates proinflammatory lipid mediators, which induce inflammation in adipose tissue. Therefore we investigated the role of 12/15-LO activity in mouse white adipose tissue in promoting obesity-induced local and systemic inflammatory consequences. We generated a mouse model for fat-specific deletion of 12/15-LO, aP2-Cre; 12/15-LOloxP/loxP, which we call ad-12/15-LO mice, and placed wild-type controls and ad-12/15-LO mice on a high-fat diet for 16 weeks and examined obesity-induced inflammation and insulin resistance. High-fat diet-fed ad-12/15-LO exhibited improved fasting glucose levels and glucose metabolism, and epididymal adipose tissue from these mice exhibited reduced inflammation and macrophage infiltration compared to wild-type mice. Furthermore, fat-specific deletion of 12/15-LO led to decreased peripheral pancreatic islet inflammation with enlarged pancreatic islets when mice were fed the high-fat diet compared to wild-type mice. These results suggest an interesting crosstalk between 12/15-LO expression in adipose tissue and inflammation in pancreatic islets. Therefore, deletion of 12/15-LO in adipose tissue can offer local and systemic protection from obesity-induced consequences, and blocking 12/15-LO activity in adipose tissue may be a novel therapeutic target in the treatment of type 2 diabetes.